2011
DOI: 10.1038/pr.2011.544
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training Surface in Agility of Prepubescent Volleyball Players

Abstract: The purpose of the present study was to examine the impact of training surface in agility of prepubescent volleyball players.Thirty female prepubescent volleyball players (age: 11.2 ± 0.6yrs) took part in this study and were randomly allocated in two groups. Group A (N=15) participated in a 10 week training programme in sand surface, while group B (N=15) participated in a same programme in land surface. Measurements of agility (T-Test & Illinois) were conducted before (pre) and after (post) the training period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Controvesly, Gortsila et al. 41 found on a sand surface resulted in significant improvements in agility tests (T-Test and Illinois test) conducted on both sand and firm surfaces, suggesting that the physiological and biomechanical adaptations unique to sand training can also have a positive effect on firm-ground agility performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controvesly, Gortsila et al. 41 found on a sand surface resulted in significant improvements in agility tests (T-Test and Illinois test) conducted on both sand and firm surfaces, suggesting that the physiological and biomechanical adaptations unique to sand training can also have a positive effect on firm-ground agility performance.…”
Section: Discussionmentioning
confidence: 99%
“…Asadi et al 40 argued that to change direction faster, it is desirable to shorten ground contact time, thus facilitating eccentric deceleration of the body's center of mass and consequently enhancing the propulsive phase. Controvesly, Gortsila et al 41 found on a sand surface resulted in significant improvements in agility tests (T-Test and Illinois test) conducted on both sand and firm surfaces, suggesting that the physiological and biomechanical adaptations unique to sand training can also have a positive effect on firm-ground agility performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, jump training on a lower impact surface could hinder muscular adaptations. However, previous research has demonstrated improvements in firm ground performance following a training stimulus on sand in a number of tasks (jumping, running, agility, strength) [24][25][26][27] , with adaptations such as enhanced motor unit recruitment and increased activation of synergists amongst the proposed mechanisms cited. 27 Furthermore, Pinnington et al 23 muscles, as well as elevated gastrocnemius activity in reducing ACL injury risk has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evidence of improvements transferring to future firm ground performance in jumping as well as running, agility, and strength tasks has been well documented. [24][25][26][27] Recent work using 3D motion capture demonstrated that the knee abduction moment (KAM), a significant predictor of knee valgus 9,12 and subsequent ACL injury risk was reduced on a sand compared to a firm surface during a single leg jump task. 28 However, the magnitude of the effect of sand on landing knee valgus specifically is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative, although less explored, practice that has the potential to positively influence performance while avoiding some of the negative physiological consequences of hypoxia is sand training [ 6 , 7 ]. Evidence suggests that the unique training adaptations for sand may have a positive influence on endurance performance [ 8 , 9 ]. Sand surfaces may provide a training stimulus that elicits a higher energetic cost with less ground reaction force compared to the more traditional training surfaces, such as synthetic fabrics or grass [ 10 ].…”
Section: Introductionmentioning
confidence: 99%